2019
DOI: 10.1038/s41598-019-39092-7
|View full text |Cite
|
Sign up to set email alerts
|

Artery targeted photothrombosis widens the vascular penumbra, instigates peri-infarct neovascularization and models forelimb impairments

Abstract: The photothrombotic stroke model generates localized and reproducible ischemic infarcts that are useful for studying recovery mechanisms, but its failure to produce a substantial ischemic penumbra weakens its resemblance to human stroke. We examined whether a modification of this approach, confining photodamage to arteries on the cortical surface (artery-targeted photothrombosis), could better reproduce aspects of the penumbra. Following artery-targeted or traditional photothrombosis to the motor cortex of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 62 publications
3
72
1
4
Order By: Relevance
“…We did not measure motor deficits in this study. Recent studies showed that the artery targeted photothrombosis of similar and larger sizes than those induced in this study led to forelimb impairments in skilled reaching tasks but were difficult to detect using less sensitive behavioral assessments (17,40). Further investigations that combine sensitive behavioral assessments and simultaneous measurements of neuronal structural changes and electrical activities will help to elucidate the underlying mechanisms of functional recovery.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…We did not measure motor deficits in this study. Recent studies showed that the artery targeted photothrombosis of similar and larger sizes than those induced in this study led to forelimb impairments in skilled reaching tasks but were difficult to detect using less sensitive behavioral assessments (17,40). Further investigations that combine sensitive behavioral assessments and simultaneous measurements of neuronal structural changes and electrical activities will help to elucidate the underlying mechanisms of functional recovery.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, this refined model of photothrombosis produces a more graded vascular penumbra than traditional photothrombosis while maintaining the ability to create localized infarcts (17). The conventional view of brain injury is that the magnitude of the deficit is coarsely correlated to the infarct size when controlled for other influences including age, morbidity and stroke locations (35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations